Les enjeux de la patrimonialisation du parc historique de la canne-à-sucre en Haïti - Jerry Michel (Articulo: Journal of Urban Research, 2014)
Access to the Haitian past slave and colonial system through memory, history or culture, can proceed from the existing colonial Habitations, which are characterized by different stages of patrimonialisation. Among them, the historical Park of the sugarcane, a former colonial agricultural exploitation, has been transformed into a museum. It can thus be considered as a “lieu de mémoire” according to Pierre Nora’s understanding of the expression (1984). Such a reconstitution consists in the exhibition of objects, words, images, conceived as symbolic and material “traces” of the past (Chamoiseau 1997), as witnesses of the domestic (Rautenberg 2003), or as a familial memory (Muxel 2003). Making a museum appears to be also a process of legitimation, through remembrance, of a certain version of the past and of claims on identity. Because it encompasses historical, memorial, patrimonial, urban, pedagogical and cultural dimensions, it can be taken as a significant case study in order to question the links between memory, history and culture in a postcolonial and post-slavery society. This paper results from an ethnographical and sociological research (archives, mass media reports, observations, photography and interviews) conducted between 2011 and 2013 with individuals, from different backgrounds, familiar with the place. It shows that this “haut-lieu” of Haitian social history puts into question the relation between the slavery-based colonial past and a perpetually framing and reframing of the present. Empirical material’s sociological analysis allows figuring out how this cultural center-museum (Vergès 2012) contributes to the invisibilisation of the slave-based social relations while it demonstrates the hegemony of economic, political and cultural elites in the Haitian society.